2020
DOI: 10.3390/jcm9082593
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Outcomes after Normal Clinical and Ultrasound Findings in Young Women with Chronic Pelvic Pain: A Cross-Sectional Study

Abstract: Chronic pelvic pain (CPP) is one of the most common chronic pain problems experienced by women, with prevalence rates comparable to asthma and back pain. However, it is poorly understood and causative pathology is only seldom found. We aimed to establish prevalence of abnormal findings at diagnostic laparoscopy in young women with CPP after normal findings at clinical examination and pelvic ultrasound scan. Information was retrospectively collected on all laparoscopies undertaken on women aged 16–30 years with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…At present, evidences on the relationship between endometriosis and asthma in women are limited and inconsistent. Tempest et al [25] retrospectively collected information on females aged 16-30 years from the Liverpool Women's Hospital, finding that women with endometriosis who underwent laparoscopy were observed to have higher odds of asthma than women without endometriosis. Similarly, in the present study, we found a positive association between endometriosis and asthma in a representative population of the U.S., after adjusting for relevant covariates.…”
Section: Discussionmentioning
confidence: 99%
“…At present, evidences on the relationship between endometriosis and asthma in women are limited and inconsistent. Tempest et al [25] retrospectively collected information on females aged 16-30 years from the Liverpool Women's Hospital, finding that women with endometriosis who underwent laparoscopy were observed to have higher odds of asthma than women without endometriosis. Similarly, in the present study, we found a positive association between endometriosis and asthma in a representative population of the U.S., after adjusting for relevant covariates.…”
Section: Discussionmentioning
confidence: 99%
“…Tempest et al diagnosed endometriosis in 20% patient with CPP. In their study, most of laparoscopies carried out on young women with CPP showed no significant clinical stigmata of pelvic pain [ 22 ]. The nature of the pain seems to be of greater importance.…”
Section: Discussionmentioning
confidence: 99%
“…In symptomatic women, previously reported incidence of endometriosis is higher, up to 70% [ 24 ]. In a recent cohort of young women with normal ultrasound findings and pelvic gynaecological examination, endometriosis was diagnosed in 20% [ 25 ]. The incidence of surgically diagnosed endometriosis in our patient cohort is less, similar to the background population rate of 10–15% [ 26 ].…”
Section: Discussionmentioning
confidence: 99%